Linking The Role of Digital Marketing and E-Commerce on Performance Marketing - Praditya, Rayyan Aqila (UJoST- Universal Journal of Science and Technology, 2024)
The aim of this research is to determine and analyze the influence of Digital Marketing on Performance Marketing, the influence of E-Commerce on Performance Marketing, and the influence of Digital Marketing and E-Commerce together on Performance Marketing. This quantitative study used analytical techniques and SmartPLS 4.0 software on 543 business actors. The research results show that digital marketing and online shop e-commerce platforms have an important role in expanding marketing reach and increasing sales of Sidoarjo souvenirs. However, its use is still not optimal for most MSMEs. The challenges faced regarding the adoption of digital marketing are the lack of knowledge and finances. Further training and assistance is needed so that the implementation of digital marketing strategies is more optimal. Digital marketing has a positive effect on Performance Marketing, E-commerce has a positive effect on Performance Marketing, Digital Marketing and E-Commerce have a joint effect on Performance Marketing.